Tall story [compact disc, unabridged] - Gourlay, Candy (Random House/Listening Library, 2012)
Sixteen-year-old Bernardo, who is eight feet tall and suffers from a condition called Gigantism, leaves the Philippines to live with his mother's family in London, much to the delight of his thirteen-year-old half sister Andi, a passionate basketball player.